Characteristics of laminar flow and heat transfer in microchannel heat sink with triangular cavities and rectangular ribs. (July 2016) - Li, Y.F.; Xia, G.D.; Ma, D.D.; Jia, Y.T.; Wang, J.
Highlights: A new microchannel with triangular cavities and rectangular ribs is presented. The combined effects of cavities and ribs are studied. The heat transfer mechanism of microchannel is analyzed by entropy generation. The geometric parameters of the new microchannel are discussed. The new microchannel yields the best overall performance with η = 1.619 at Re = 500. Abstract: A novel microchannel heat sink with triangular cavities and rectangular ribs (TC–RR) is presented and the characteristics of fluid flow and heat transfer are studied numerically for Reynolds number ( Re ) ranging from 173 to 635. The effects of cavities and ribs on the Nusselt number and friction factor are investigated. The method of entropy generation minimization is also adopted to analysis the thermal performance of the micro heat sink and the mechanism of heat transfer enhancement. The overall performance of the new micro heat sink is assessed based on thermal enhancement factor and augmentation entropy generation number. The results show that the TC–RR microchannel obtains significant heat transfer enhancement attributed to the interruption and redevelopment of thermal boundary layer, the intensified mainstream disturbance and the chaotic mixing between the cold and hot water. In addition, the influence of relative rib width ( α ) and relative cavity width ( β ) on the flow and heat transfer performance is investigated. The thermal enhancement factor for TC–RR microchannel with α = 0.3 and β = 2.24 achieves 1.619 at Re = 500. Due to more uniform temperature of bottom surface, less irreversibility and better heat transfer performance, the novel micro heat sink is more promising for microelectronic cooling system.